2012
DOI: 10.1051/epjconf/20122601054
|View full text |Cite
|
Sign up to set email alerts
|

The virtual fields method applied to spalling tests on concrete

Abstract: Abstract. For one decade spalling techniques based on the use of a metallic Hopkinson bar put in contact with a concrete sample have been widely employed to characterize the dynamic tensile strength of concrete at strain-rates ranging from a few tens to two hundreds of s −1 . However, the processing method mainly based on the use of the velocity profile measured on the rear free surface of the sample (Novikov formula) remains quite basic and an identification of the whole softening behaviour of the concrete is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The non-linear constitutive behaviors may suggest that the assumption of the linear-elastic constitution of concrete may be invalid for the concrete-like materials. This is supported by previous studies which also report similar non-linear behaviors in concrete-like materials [33,52,53]. One may expect that these non-liner behaviors contribute to the significant reduction in the attenuation and propagating speed of stress wave under high loading-rate conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The non-linear constitutive behaviors may suggest that the assumption of the linear-elastic constitution of concrete may be invalid for the concrete-like materials. This is supported by previous studies which also report similar non-linear behaviors in concrete-like materials [33,52,53]. One may expect that these non-liner behaviors contribute to the significant reduction in the attenuation and propagating speed of stress wave under high loading-rate conditions.…”
Section: Discussionsupporting
confidence: 87%
“…[ 53 ] One of the first extensions of VFM to dynamic loading conditions was presented in the seminal article published in Strain 2012. [ 54 ] The authors showed that the right‐hand‐side term of Equation (3) can be used as an advantage since the contribution of the inertial component defined through the measured acceleration maps present an image embedded load cell and in that case no external load measurement is needed. Consequently, an appropriate choice of virtual fields can lead to a direct identification of either material stiffness or average uniaxial stress measurement.…”
Section: Methodsmentioning
confidence: 99%
“…As explained in Pierron and Forquin, [ 54 ] following the schematic presentation of the framed spalling sample with the flattened surface (Figure 3), the resulting stress field will be mainly uniaxial, and a virtual displacement field can be chosen so that it depends only on the axial direction. Consequently, this choice can be made so to cancel out the contribution of other stress tensor components as follows: VF1:ux=ffalse(xfalse)uy=0εx=ffalse(xfalse)εy=0εxy=0, where f ( x ) is a continuous and differentiable function of x , with condition f ( x = l ) = 0 which avoids having a contribution of the traction force at the boundary opposite to the free‐end ( x = 0).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations